2012
DOI: 10.1261/rna.033134.112
|View full text |Cite
|
Sign up to set email alerts
|

The box C/D sRNP dimeric architecture is conserved across domain Archaea

Abstract: Box C/D small (nucleolar) ribonucleoproteins [s(no)RNPs] catalyze RNA-guided 29-O-ribose methylation in two of the three domains of life. Recent structural studies have led to a controversy over whether box C/D sRNPs functionally assemble as monomeric or dimeric macromolecules. The archaeal box C/D sRNP from Methanococcus jannaschii (Mj) has been shown by glycerol gradient sedimentation, gel filtration chromatography, native gel analysis, and single-particle electron microscopy (EM) to adopt a di-sRNP architec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
36
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(38 citation statements)
references
References 63 publications
(139 reference statements)
2
36
0
Order By: Relevance
“…Nop56 and Nop58 have extensive coiled-coil domains with which they heterodimerize. Although there are both single-particle electron microscopic and crystallographic structures of complete enzymatically active archaeal box C/D s(no)RNPs (Bleichert et al 2009;Bleichert and Baserga 2010;Lin et al 2011;Bower-Phipps et al 2012), no structure yet exists for the yeast box C/D snoRNP.…”
Section: Pre-rrna Processing Can Occur Cotranscriptionallymentioning
confidence: 99%
“…Nop56 and Nop58 have extensive coiled-coil domains with which they heterodimerize. Although there are both single-particle electron microscopic and crystallographic structures of complete enzymatically active archaeal box C/D s(no)RNPs (Bleichert et al 2009;Bleichert and Baserga 2010;Lin et al 2011;Bower-Phipps et al 2012), no structure yet exists for the yeast box C/D snoRNP.…”
Section: Pre-rrna Processing Can Occur Cotranscriptionallymentioning
confidence: 99%
“…The model was derived in the absence of the substrate RNAs and the guide sRNA was not visible in the microscopy images, thus preventing any conclusion on the location of the substrates D and D ′ . Later, the same group demonstrated that all box C/D sRNPs from Archaea are di-RNPs, while a mono-RNP is obtained only when assembling the complex around an artificial two-piece guide sRNA (Bower-Phipps et al 2012).…”
Section: Discussionmentioning
confidence: 99%
“…This mechanism is incompatible with the RNA-swapped model for dimeric C/D RNP. C/D RNA has proposed to be swapped between two different protein complexes in the di-RNP (34)(35)(36)(37)(38), rather than associating with the same Nop5 dimer as shown in the mono-RNP structure (30). It also has been argued that the RNA-swapped di-RNP model is advantageous for accommodating long guide-substrate duplexes compared with the mono-RNP model.…”
Section: Significancementioning
confidence: 99%